European travel for the monstrous gentlewoman - Goss, Theodora (Saga Press, 2018)
Mary Jekyll<U+2019>s life has been peaceful since she helped Sherlock Holmes and Dr. Watson solve the Whitechapel Murders. Beatrice Rappaccini, Catherine Moreau, Justine Frankenstein, and Mary<U+2019>s sister Diana Hyde have settled into the Jekyll household in London, and although they sometimes quarrel, the members of the Athena Club get along as well as any five young women with very different personalities. At least they can always rely on Mrs. Poole. But when Mary receives a telegram that Lucinda Van Helsing has been kidnapped, the Athena Club must travel to the Austro-Hungarian Empire to rescue yet another young woman who has been subjected to horrific experimentation. Where is Lucinda, and what has Professor Van Helsing been doing to his daughter? Can Mary, Diana, Beatrice, and Justine reach her in time? Racing against the clock to save Lucinda from certain doom, the Athena Club embarks on a madcap journey across Europe. From Paris to Vienna to Budapest, Mary and her friends must make new allies, face old enemies, and finally confront the fearsome, secretive Alchemical Society. It<U+2019>s time for these monstrous gentlewomen to overcome the past and create their own destinies.